Black pioneers of science and invention - Haber, Louis (San Diego Harcourt Brace Jovanovich, 1991)
Traces the lives of fourteen black scientists and inventors who have made significant contributions in the various fields of science and industry.
Reprint. Originally published: New York : Harcourt, Brace & World, 1970.
"An Odyssey book."
Includes bibliographical references (p. 245-254) and index.
Keywords: African American scientists -- Biography -- Juvenile literature; African American inventors -- Biography -- Juvenile literature; Scientists; Inventors; African Americans -- Biography